Optimization Approach to Hazard Prevention Budgeting Problem - Asawarungsaengkul, Krisada; Nanthavanij, Suebsak (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
An analytical approach to optimally allocate the hazard prevention budget so as to eliminate or reduce hazard exposures in the industrial workplace is presented. Two hazard control approaches are considered: engineering approach and administrative approach. For the engineering approach, we consider controlling at the source of hazard and blocking the hazard along the transmission path. For the administrative approach, only job rotation is considered. From the given hazard prevention budget, four optimization models are sequentially employed to select appropriate hazard controls without exceeding the allocated budget. A sensitivity analysis is performed to study how the hazard prevention solution is affected by the budget portion allocated to engineering controls.